'It's silly these doors don't open': a six-year-old girl emerges from a chronic state of emotional withdrawal. Issue 2 (3rd May 2016) - Mooney, Ruth
Abstract : This clinical paper explores the way in which the first two years of a long-term psychotherapy helped six-year-old Anna to lessen her retreat into a chronic withdrawn emotional state. Over the course of the first year she would occasionally pick up the fridge from the doll's house and try to open the doors, but because the fridge was actually a block of wood the doors could not open. In treatment, this inquiry came to represent the difficulties of engaging and making contact with a baby who found it very hard to feed. The author describes how, as Anna entered into a therapeutic relationship, it slowly became clear that there was an inner world jam-packed with persecutory anxieties and a family history of unmourned loss and trauma. Through fear Anna slammed the doors to her mind – to knowing herself – and by not feeding, Anna starved herself of opportunities for mental growth. It took some time for her to state, "it's silly these doors don't open, they should". In the discussion of this clinical material the author draws on the work of Francis Tustin, Alessandra Piontelli and Marguerite Reid to consider the link between intergenerational and prenatal trauma and subsequent emotional disturbance in the child.